Effect of Preconception Male Cocaine Use on Post-weaning Thigmotaxic Behavioral Activity of Offspring in Congenic, Lean LA/Ntul//-cp Rats: Thigmotaxis in Cocaine Exposed Offsping - Tulp, Orien L (British Journal of Healthcare and Medical Research, 2025)
Because mammalian sperm have been found to contain opioid binding sites, there exists a potential for opioids to impact on early embryonic development of offspring in zygote exposed naïve, opioid-free dams. To determine the effects of chronic cocaine use by males on the offspring of naïve females, groups of adult 60 day old lean male LA/Ntul//-cp rats were reared from weaning on standard Purina chow and house water, and administered 0 or 30 mg of cocaine HCL for 90 ±2 days to encompass the duration of spermatogenesis, then mated with 82±3 day old naïve, normally reared virgin females of the same strain that had never been exposed to the opioid or related compounds. Behavioral activity of offspring was assessed by subjecting the postweaning offspring at 21 days of age with a Stoelting activity wheel and a Calvin Hall open access field test. Offspring were found to exhibit fewer open field square and exploratory activity at 21 days of age than offspring sired by similar aged and reared non-cocaine treated drug free males. These observations suggest that opioid addiction of male partners may impact the early post-weaning thigmotaxis behavioral activity of offspring of naive, drug free dams compared to drug free controls, and may predispose the offspring of opiate treated males to additional opiate-linked behavioral deficits during later stages of growth, maturation and development.